Verres incolores de l'antiquité romaine en Gaule et aux marges de la Gaule - Foy, Danièle 1951- (Archaeopress Publishing, 2018)
Colourless glass became prominent between the middle of the 1st century AD and the beginning of the 4th century. This text reflects the diversity of glass and is designed as a practical manual divided into three parts: assemblages, typological catalogue, chemical analyses
Online-Ressource einer mehrteiligen Monografie, die Printausgabe ist in zwei Teilen erschienen
Keywords: Geschichte 100 v.Chr.-400; Glassware, Roman; Glassware, Roman / France; Funde; Glas; Gallien